2022
DOI: 10.1097/rli.0000000000000881
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Physicochemical Properties, Pharmacokinetics, Biodistribution, Toxicity, and Contrast-Enhanced Cancer MRI of a Cancer-Targeting Contrast Agent, MT218

Abstract: Objectives Preclinical assessments were performed according to the US Food and Drug Administration guidelines to determine the physicochemical properties, pharmacokinetics, clearance, safety, and tumor-specific magnetic resonance (MR) imaging of MT218, a peptidic gadolinium-based MR imaging agent targeting to extradomain B fibronectin for MR molecular imaging of aggressive tumors. Materials and Methods Relaxivity, chelation stability, binding affinity, safety-related target… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
43
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 10 publications
(44 citation statements)
references
References 63 publications
1
43
0
Order By: Relevance
“…In contrast, MRMI of fibrin-FN clots with a CREKA targeted agent is not able to differentiate PC3 and LNCaP tumors, possibly because the clots are formed by accumulations of the plasma proteins in the tumor periphery rich of angiogenic blood vessels. 1 The optimized targeted agent MT218 was able to produce robust signal enhancement in rats bearing PC3 tumors at substantially reduced doses of 0.02 and 0.04 mmol/kg, producing a 3-and 6-fold CNR, respectively, 4 The preclinical studies have demonstrated that small peptide targeted GBCAs specific to abundant targets in the tumor ECM are able to generate detectable MRI signal enhancement for delineation of primary tumors and micrometastases in rodent models. The lead targeted GBCA, MT218, shows promise for detecting several types of EDB-FN positive aggressive cancers, differentiating the tumor heterogeneity based on the EDB-FN expression levels, and to noninvasively assess the tumor response to therapies, including development of drug resistance in correlation with the biology of EDB-FN in cancer.…”
Section: ■ Characterization Of the Contrast Agentsmentioning
confidence: 99%
See 4 more Smart Citations
“…In contrast, MRMI of fibrin-FN clots with a CREKA targeted agent is not able to differentiate PC3 and LNCaP tumors, possibly because the clots are formed by accumulations of the plasma proteins in the tumor periphery rich of angiogenic blood vessels. 1 The optimized targeted agent MT218 was able to produce robust signal enhancement in rats bearing PC3 tumors at substantially reduced doses of 0.02 and 0.04 mmol/kg, producing a 3-and 6-fold CNR, respectively, 4 The preclinical studies have demonstrated that small peptide targeted GBCAs specific to abundant targets in the tumor ECM are able to generate detectable MRI signal enhancement for delineation of primary tumors and micrometastases in rodent models. The lead targeted GBCA, MT218, shows promise for detecting several types of EDB-FN positive aggressive cancers, differentiating the tumor heterogeneity based on the EDB-FN expression levels, and to noninvasively assess the tumor response to therapies, including development of drug resistance in correlation with the biology of EDB-FN in cancer.…”
Section: ■ Characterization Of the Contrast Agentsmentioning
confidence: 99%
“…Overall, MT218 has similar pharmacokinetics and clearance as other clinical macrocyclic GBCAs and no detectable brain retention and minimal retention in other organs and tissues. 4 MT218 has an excellent safety profile as demonstrated in the mandated physicochemical characterization and preclinical efficacy, pharmacokinetics, pharmacology, and safety assessments for an investigational new drug (IND) application to the FDA. IND approval is the first step in a lengthy FDA approval process for in-human use of CAs and represents a major milestone on the way to clinical development and application.…”
Section: ■ Characterization Of the Contrast Agentsmentioning
confidence: 99%
See 3 more Smart Citations